Cathodic electrogenerated chemiluminescence of tris(2, 2′-bipyridine)ruthenium(ii) and peroxydisulfate at pure Ti3C2Tx MXene electrodes. Issue 69 (30th July 2020) - Zhang, Jizhen; Kerr, Emily; Usman, Ken Aldren S.; Doeven, Egan H.; Francis, Paul S.; Henderson, Luke C.; Razal, Joselito M.
Abstract : Two-dimensional transition metal carbide (Ti3 C2 T x MXene) film as a novel electrode material for electrogenerated chemiluminescence of tris(2, 2′-bipyridine)ruthenium(ii ) and peroxydisulfate. Abstract : We demonstrate the first use of pure films of two-dimensional (2D) transition metal carbides and nitrides (Ti3 C2 T x MXene) as an electrode material for electrogenerated chemiluminescence (ECL). The Ti3 C2 T x MXene electrodes exhibited excellent electrochemical stability in the cathodic scan range and produced bright reductive–oxidation ECL using peroxydisulfate as a co-reactant with the tris(2, 2′-bipyridine)ruthenium(ii ) ([Ru(bpy)3 ] 2+ ) luminophore.